Saying thank you - Reece, Colleen L.; Connelly, Gwen (Elgin, Ill. : Child's World, 1983)
Saying thank you makes everyone feel better; and there are many things to feel thankful for, too.
Originally published: Elgin, Ill. : Child's World, 1982. (What does it mean?)
Keywords: Gratitude; Children; Gratitude; Conduct of life